Additions of new species to the Paratanaoidea (Crustacea, Tanaidacea) of Taiwan - Tzeng, You-Wei; Hsueh, Pan-Wen (Zootaxa, 2021)
The present study reports one new species of the Family Leptocheliidae Lang, 1973 and one new species of Pseudotanaidae Sieg, 1976 from Taiwan. The leptocheliid Paraleptochelia setosa sp. nov. can be differentiated from its congeners by both sexes having a two-articled exopod and five-articled endopod on the uropod, the female having coupling hooks on the inner margin of the maxilliped endite, the male having a five-articled antennule flagellum, and cheliped fixed finger with one large subtriangular denticle on the incisive margin in some individuals. The pseudotanaid Akanthinotanais pedecerritulus sp. nov. can be distinguished from its congeners by pereopods 2 and 3 having a sigmoid (S-shaped) dactylus, a unique feature in Akanthinotanais. The family Pseudotanaidae and the two genera are reported from Taiwan for the first time, as are the two genera for the West Pacific. Key morphological characters of all known Paraleptochelia and Akanthinotanais species are tabulated.